Modeling Human?System Interaction : Philosophical and Methodological Considerations, with Examples. - Sheridan, Thomas B. (Stevens Institute Series on Complex Systems and Enterprises Ser., 2016)
This book presents theories and models to examine how humans interact with complex automated systems, including both empirical and theoretical methods.-Provides examples of models appropriate to the four stages of human-system interaction -Examines in detail the philosophical underpinnings and assumptions of modeling -Discusses how a model fits into "doing science" and the considerations in garnering evidence and arriving at beliefs for the modeled phenomena Modeling Human-System Interaction is a reference for professionals in industry, academia and government who are researching, designing and implementing human-technology systems in transportation, communication, manufacturing, energy, and health care sectors.